The present situation of Stubborn in Spain - Moreno, Pedro; Cambra, Mariano; Martínez, E.; Salcedo, Carmina I. (I.S.C.N (International Society of Citrus Nurserymen), 2021)
A survey for Stubborn was carried out in different citrus areas in the Northern of Valencia. Graft transmission experiments to indicator plants grown in a warm greenhouse failed to show symptoms of stubborn. Assays to culture Spiroplasma citri from young shoots taken from field trees or from graf-imoculated greenhouse plants also gave negative results. A culture of Spiroplasma was obtained from three fruits of a single tree in 1980. The only visible symptom expressed by this infected tree was the presence of some small slightly misshapen fruits showing green coloration at the stylar end. No positive culture could be obtained from 210 fruits taken from 52 trees of the same orchard or from 83 fruits taken from 28 trees with declined appearance in other citrus plantings. Assays to detect Spiroplasma by the ELISA technique in young shoots of all the indicator plants inoculated from field trees were unsucessful, but positive ELISA reaction was obtained with young shoots of infected control citrus plants grown at the warm greenhouse. ELISA was unable to detect Spiroplasma in fruits from the single infected tree found in the survey. Trials to detect spread of Spiroplasma in different citrus plantings by growing periwinkle plants in or beside those plantings were unsuccessful though some periwinkles were affected by different MLO-associated diseases. Our results suggest that citrus stubborn may have a very low incidence and a very restricted diffusion rate in Valencia. Therefore stubborn appears to be of no economic importance in this citrus area.